Women Leadership: Telaah Kapasitas Perempuan Sebagai Pemimpin - Reny Yulianti; Dedy Dwi Putra; Paulus Diki Takanjanji (Universitas Islam Darul Ulum Lamongan, 2018)
The challenge of reform and globalisation demands a leader able to manage theOrganization well with everything needed heed for the sake of the achievement goals ofthe organization. Gender differences in leadership is no longer in question. This isevidenced by the women has a characteristic form of capital to become a leader as shownR.A. Kartini as role model for women in Indonesia. Women also have the ability to be aleader who subsequently made the purpose of writing to know the characteristics ofwomen who can bolster the effectiveness of leadership. The results of the deliberations ofthat is there are two types of female leadership style that is transformational andfeminism. As for the support of the leadership style that is the ability to persuade, provethe critics wrong, team work Spirit, has a strong charisma, risk-taking, multitasking andimpatient. By looking at the capabilities of women women should've got a central positionin the development of society